The Influence of the Work Environment and Career Development on Employee Work Productivity at PT. PG Rajawali II Unit Jatitujuh Majalengka - Fia Dayanti Aprilyani; Editya Nurdiana (Interdisciplinary Social Studies, 2026)
Employee work productivity is one of the main determinants in supporting the success and competitiveness of companies, especially in the manufacturing industry sector, which strives for a high level of efficiency and performance. The achievement of employee work productivity is influenced by various internal organizational factors, namely the conditions of the work environment and the career development system. This research intends to examine the influence of Work Environment and Career Development on employee work productivity at PT PG Rajawali II Jatitujuh Majalengka Unit. Data accumulation was carried out through a survey using a systematic questionnaire disseminated to 133 permanent employee respondents, with a sample determination technique using probability sampling based on the Slovin formula. The data analysis was conducted using the Structural Equation Modeling method based on Partial Least Squares (SEM-PLS) with SmartPLS software, accompanied by testing the validity and reliability of the research instruments. The results of the analysis prove that the Work Environment has a positive and significant effect on the work productivity of employees, as well as Career Development, which is shown to have a positive and significant influence on work productivity. These findings prove that the creation of a conducive work environment and the implementation of a clear and structured career development system play an important role in increasing employee work productivity.